1989
DOI: 10.3354/meps051057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity changes on zinc uptake and regulation by the decapod crustaceans Palaemon elegans and Palaemonetes varians

Abstract: ABSTRACT-The decapod crustaceans Palaernon elegans Rathke and Palaernonetes varians (Leach) regulate their body concentrations of zinc to an approximately constant level (ca 76 to 82 and 90 to 99 11g Zng-' dry wt respectively) when exposed to a wide range of dissolved Zn concentrations, until a threshold dissolved concentration when regulation breaks down and net accumulation of body Zn begins. This threshold concentration decreases with decrease in salinity, from 100 "/u SW to 50 O/ O SW in the case of P. ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 16 publications
5
37
3
Order By: Relevance
“…This result was similar to the studies on amphipods (Orchestia gammarellus) by Rainbow et al 40 and Rainbow and Kwan 41 , which found that decreases in salinity produced predictable increases in metal uptake rate. This result was different from the study in Palaemon elegans and Palaemonetes varians by Nugegoda and Rainbow 42,43 that decreases in salinity could decrease concentration of metals. This is similar to the study by Xiaobo et al 12 in molluscs (Onchidium struma) that Cu is a cofactor for regulating the activity of Cudependent enzymes 12,44 and an essential component required for the synthesis of haemocyanin 45 .…”
Section: Discussioncontrasting
confidence: 54%
“…This result was similar to the studies on amphipods (Orchestia gammarellus) by Rainbow et al 40 and Rainbow and Kwan 41 , which found that decreases in salinity produced predictable increases in metal uptake rate. This result was different from the study in Palaemon elegans and Palaemonetes varians by Nugegoda and Rainbow 42,43 that decreases in salinity could decrease concentration of metals. This is similar to the study by Xiaobo et al 12 in molluscs (Onchidium struma) that Cu is a cofactor for regulating the activity of Cudependent enzymes 12,44 and an essential component required for the synthesis of haemocyanin 45 .…”
Section: Discussioncontrasting
confidence: 54%
“…The failure of low salinities to increase Zn influx, in contrast with Cd and Cr, is contradictory to other studies that report increased Zn influx by crustaceans and molluscs with decreased salinity (e.g. Nugegoda & Rainbow 1989a, b, Wanq et al 1996. It is also not consistent with an overall increased gill permeability at lower salinities, which was one explanation for the Cr results.…”
Section: Daycontrasting
confidence: 52%
“…1990, Rainbow et al 1993), or changes in salinity that alter concentrations of inorganic anions such as chloride that complex particular metal ions (Nugegoda & Rainbow 1989a,b, Rainbow et al 1993, Rainbow & Black 2002. For example, dissolved cadmium in seawater exists mostly as chloro-complexes (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Correspondingly physicochemical factors that affect the availability of the free metal ion in solution have been shown to affect trace metal uptake rates by aquatic invertebrates (Rainbow 1997, Rainbow & Black 2002. Such physicochemical factors include the presence of chelating agents that reduce the availability of free metal ions (Nugegoda & Rainbow 1988, O'Brien et al 1990, Rainbow et al 1993, or changes in salinity that alter concentrations of inorganic anions such as chloride that complex particular metal ions (Nugegoda & Rainbow 1989a,b, Rainbow et al 1993, Rainbow & Black 2002. For example, dissolved cadmium in seawater exists mostly as chloro-complexes (e.g.…”
Section: Introductionmentioning
confidence: 99%